The language of accounting in English (Prentical Hall, 1977)
This book is good for those that want to obtain general vocabulary words and survey of USA accounting methods. 2. This is not the book for someone who is already an accountant from another country who needs to translate accounting vocabulary or jargan beyond generalities for a US job